Experimental evaluation of an inflatable solar bag dryer for cocoa drying (Nexo Revista Científica, 2023)
In this work, a prototype inflatable solar bag dryer was used to evaluate the drying of freshly fermented cocoa. Said dryer consists of a semi-cylindrical tunnel with a black waterproof vinyl canvas bottom and a translucent plastic cover; both parts joined by a zipper. This low-temperature direct and active hybrid solar dryer has a total length of 6.15 m and a width of 2.00 m; useful drying area 8.82 m2; capacity 177 kg of freshly fermented cocoa. Its photovoltaic system supplies energy to a fan and an electrical resistance. During the evaluation, the humidity of 84.60 kg of freshly fermented cocoa was reduced in five days from 50% wb to 7.4% wb; keeping its temperature always below 65 °C. As it passed through the equipment at 0.017 m/s, the drying air increased its temperature by up to 20 °C and reduced its relative humidity by up to 30 %. The average energy efficiency of the dryer decreased as grain moisture decreased: from 72.63%, on the first day, to 8.51%, on the fifth day. The physical-sensory evaluation of the obtained cocoa indicated that it is acceptable for making chocolate.